Preclinical evidence and possible mechanisms of β-asarone for rats and mice with Alzheimer’s disease: A systematic review and meta-analysis - Du, Xin-Yuan; Cao, Yu-Shuang; Yang, Juan; Guo, Li-Chen; Zhang, Tong; Yuan, Qing; Chen, Xi; Hu, Li-min (Frontiers in Pharmacology, 2022)
Background: Currently, there are many different drugs to improve Alzheimer's disease (AD) from different pathways. As supplement and alternative medicine, Traditional Chinese medicine(TCM) targets multiple pathways which may be different from classical western medicine, which may be orchestrated with western medicine to materialize multiplying efficacy in AD patients. Objective: To investigate the therapeutic effect and assess the available preclinical evidence and possible mechanisms of β-asarone which was extracted from Acorus gramineus Soland (araceae, AGS) for AD based on rats and mice animal models. Method: PubMed, Embase, Scopus, Cochrane Library, BIOSIS Previews, Web of Science, EBSCO, Google Scholar were searched from inception to 5 May 2022. Rat and mice experiment assessing therapeutic effects of β-asarone for AD were included. Primary outcomes were neuroethology, including escape latency, times of crossing platform.etc. Second outcomes were cell apoptosis, including Bax, Bcl-2.etc. Weighted Mean Difference (WMD) was generated for continuous variables. Meta-analysis was performed using software STATA version 16.0 MP. Result: For the primary endpoint, compared with modeling group, β-asarone significantly decreased the escape latency (WMD=-12.61, 95CI%: -18.66 to -6.57), increased the times of crossing platform (WMD=1.50, 95CI%: 0.31 to 2.70). For the secondary endpoint, β-asarone remarkably reduced the relative expression of amyloid precursor protein(APP) (WMD=-2.25, 95CI%: -2.49 to -2.01), decreased the expression of apoptosis related protein Associated X Protein(Bax) (WMD=- 2.40, 95CI%: -3.51 to -1.29), lowered the expression of apoptosis related protein B-cell lymphoma-2(Bcl-2) (WMD=0.42, 95CI%: 0.38 to 0.46), decreased the signal pathway related proteins phosphatidylinositol-3-kinase/protein kinase B(PI3K/AKT) (WMD= - 0.70, 95CI%: -0.93 to -0.47) over the control group. Conclusion: β-asarone spectacularly improved the learning ability and memory in rats and mice, which might be correlated with its potential neuroprotective effect through multiple signaling pathways.